Psychological and sexological assessment of patients with chronic prostatitis - Konstantinos Stamatiou; Vittorio Magri; Margherita Trinchieri; Alberto Trinchieri; Gianpaolo Perletti (Archivio Italiano di Urologia e Andrologia, 2024)
Purpose: Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) is characterized by a multiform clinical presentation requiring a differentiated treatment based on different phenotypes including the psychosocial and sexual domains. The aim of this study was assessing the complex correlations between somatic, psychological, and sexual symptoms of CP/CPPS patients. Materials and methods: We performed a cross-sectional study on patients attending a Prostatitis Clinic. Patients were administered the following questionnaires: National Institutes of Health- Chronic Prostatitis Symptom Index (NIH-CPSI), International Prostate Symptom Score (IPSS), International Index of Erectile Function (IIEF), Premature Ejaculation Diagnostic Tool (PEDT), Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder 7-item (GAD-7), Oxford Happiness Questionnaire (OHQ), and Temperament Evaluation of Memphis, Pisa, Paris and San Diego Autoquestionnaire (TEMPS-A). Results: Linear regression analyses show highly significant correlations between scores of the NIH-CPSI and the scores of the GAD-7, PHQ-9 and OHQ psychometric questionnaires. IPSS scores correlate significantly with the psychometric scores only when a non-parametric analysis is performed. IIEF and PEDT sexual function scores did not correlate with any of the psychometric tests. NIH-CPSI scores correlate positively with most of the TEMPS-A profiles but the hyperthymic profile correlated negatively with the total and QoL NIH-CPSI and with PEDT scores. Conclusions: Scores measuring anxiety, depression, and psychological well-being in patients with CP/CPPS are strictly correlated with prostatitis-like symptoms although they are poorly correlated with symptoms of prostatism, as measured by IPSS, and not correlated with scores of sexual dysfunctions, as measured by IIEF and PEDT. A hyperthymic temperament may increase resilience against the disease.